Applications and Impacts of Edible Coatings on Food Quality - Stéfane Smith Freire Le; Elba Santos da Boa Morte; Márcia Filgueiras Rebelo de Matos; Lílian Lessa Andrade; Kyan James Allahdadi; Maria da Conceição Pereira da Fonseca; Matos, Laise Cedraz Pinto (Food Science and Engineering, 2024)
Edible coatings are emerging as a significant trend in the food industry, driven by growing consumer interest in environmental issues, mainly due to concerns about the excessive use of plastics. This study aimed to perform an integrative review to identify the materials used to produce edible films and characterize their applicability for food quality and conservation. For this, the descriptors “edible films” or “edible coatings” and “food quality” or “food preservation” or “food safety” were used in the Science Direct database, resulting in 48 articles selected. Fruits and vegetables are the two food groups most studied with coatings based on hydrocolloids, protein, composite films, and lipids, with a greater emphasis on the positive impacts on their quality and conservation. Animal products have a higher frequency of studied antimicrobial effects. There is a diversity of materials used in coatings: vegetable-based, such as algae, mucilages, and fibers, as well as those of animal origin, such as gelatin and protein hydrolysates. Few studies have addressed sustainability concepts as final characteristics of coatings. In conclusion, edible coatings show promise for the food industry, offering benefits for both food and the environment. However, more studies are needed to fully explore their potential as replacements for conventional plastics, while ensuring safety and regulatory compliance.